Comparative Analysis of Tetra(2-naphthyl)tetracyano-porphyrazine and Its Iron Complex as Photosensitizers for Anticancer Photodynamic Therapy - Lydia N. Shestakova; Tatyana S. Lyubova; Svetlana A. Lermontova; Artem O. Belotelov; Nina N. Peskova; Larisa G. Klapshina; Irina V. Balalaeva; Natalia Y. Shilyagina (MDPI AG, 2022)
Photodynamic therapy (PDT) is a rapidly developing modality of primary and adjuvant anticancer treatment. The main trends today are the search for new effective photodynamic agents and the creation of targeted delivery systems with the function of controlling the release of the agent in the tumor. Recently, the new group of cyanoarylporphyrazine dyes was reported, which combine the properties of photosensitizers and sensors of the local microenvironment. Such unique characteristics allow the release of the photosensitizer from the transport carrier to be assessed in real time in vivo. The aim of the present work was to compare the photophysical and photobiological properties of tetra(2-naphthyl)tetracyanoporphyrazine and its newly synthesized Fe(II) complex. We have shown that the chelation of the Fe(II) cation with the porphyrazine macrocycle leads to a decrease in molar extinction and an increase in the quantum yield of fluorescence and photostability. We demonstrate that the iron cation significantly affects the rate of dye accumulation in cells, the dark toxicity and photodynamic activity, and the direction of the changes depends on the particular cell line. However, in all the cases, the photodynamic index of a metal complex was higher than that of a metal-free base. In general, both of the compounds were found to be very promising for PDT, including for the use with transport delivery systems, and can be recommended for further in vivo studies.